Percutaneous Left Atrial Appendage Ligation for Stroke Prevention in Atrial Fibrillation - Valderrábano, Miguel (Methodist Debakey Cardiovasc J, 2015)
Prevention of thromboembolic complications in atrial fibrillation remains a tremendous clinical challenge. Knowledge that the left atrial appendage (LAA) is the most common anatomical origin of cardioembolic strokes1 has been the main motivation to develop clinical and procedural strategies to exclude the LAA from the circulation, either surgically or percutaneously. This review discusses the rationale behind these strategies, their relative merits, and future prospects for LAA exclusion strategies.